2013
DOI: 10.4161/hv.26498
|View full text |Cite
|
Sign up to set email alerts
|

Optimized and enhanced DNA plasmid vector based in vivo construction of a neutralizing anti-HIV-1 envelope glycoprotein Fab

Abstract: Monoclonal antibody preparations have demonstrated considerable clinical utility in the treatment of specific malignancies, as well as inflammatory and infectious diseases. Antibodies are conventionally delivered by passive administration, typically requiring costly large-scale laboratory development and production. Additional limitations include the necessity for repeat administrations, and the length of in vivo potency. Therefore, the development of methods to generate therapeutic antibodies and antibody lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 53 publications
0
46
1
Order By: Relevance
“…The in vivo expression of antibodies against infectious diseases from a plasmid vector was first demonstrated in a human immunodeficiency virus type 1-mouse model, but the long-term persistence of the neutralizing antibody was not reported [40]. We have successfully demonstrated the maintenance of detectable neutralizing antibody (>90% plaque reduction) against DENV-1 for 3 months in mice inoculated with an antibodyexpressing plasmid, when serum samples were diluted 1:2.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The in vivo expression of antibodies against infectious diseases from a plasmid vector was first demonstrated in a human immunodeficiency virus type 1-mouse model, but the long-term persistence of the neutralizing antibody was not reported [40]. We have successfully demonstrated the maintenance of detectable neutralizing antibody (>90% plaque reduction) against DENV-1 for 3 months in mice inoculated with an antibodyexpressing plasmid, when serum samples were diluted 1:2.…”
Section: Discussionmentioning
confidence: 78%
“…1) was used and attempts to increase antibody production in mice with p7F4-IL2ss, pIRES7F4HL, or pIRES7F4LH also failed (data not shown). Further studies are required to improve the expression cassette and plasmid delivery rate, for codon optimization, and to increase the antibody half-life, as reported elsewhere [40,43,44]. Because the model antibody used in the present study (7F4) was specific for DENV-1 [27], further studies are required to identify an appropriate human neutralizing antibody clone that is broadly cross-reactive with all four DENV serotypes.…”
Section: Discussionmentioning
confidence: 85%
“…Specifically, the Kozak sequence (GCCACC) has been demonstrated to be necessary to preced the ATG start codon in order to drive protein translation 55,56 . As well, incorporation of an IgE leader sequence (MDWTWILFLVAAATRVHS) has been demonstrated to enhance translation of the The sequence was then synthesized commercially 50,54 and cloned into the pVax1 expression vector (Invitrogen) between restriction sites KpnI and NotI. The production of the DNA construct for vaccine use was performed by Aldevron (Fargo, North Dakota, US).…”
Section: Cloning Of the Consensus Leptospiral Protein Lipl45 Vaccinementioning
confidence: 99%
“…The Cluster X program (Version 1.81) was used to align the sequences and select the consensus amino acid sequence. The consensus sequence was optimized for expression, including codon and RNA optimization (Gene Optimizer™, GeneArt, Regensburg, Germany) 54 . A Kozak sequence as well as an IgE leader sequence was incorporated in the N terminal region of the construct in order to enhance the expression and ultimately immunogenicity of the plasmid based vaccine.…”
Section: Cloning Of the Consensus Leptospiral Protein Lipl45 Vaccinementioning
confidence: 99%
“…In that study it was shown that after delivery of the mAb DNA, mice were able to generate in their sera long-term expression of antibodies that were able to neutralize HIV-1 in vitro. 57 These proof-ofconcept studies suggest that this non-viral DNA plasmid delivery method might have applications in terms of targeting mAbs against a¡syn and Ab as well as other potential antigens. Even though this method has a likely better safety profile than viral vector based delivery systems, further optimization of the strategy is needed in order to generate the higher expression levels that were attained by AAV delivery methods.…”
Section: Introductionmentioning
confidence: 97%